Sistem Penegakan Hukum Pencurian Kelapa Sawit Ptpn II Dusun VI Desa Pagar Merbau II Kec. Pagar Merbau Kab. Deli Serdang: (Studi Kasus Putusan Nomor 2/Pid.C/2024/PN Lbp) - Agus Irwansyah; Muhammad Ridwan Lubi (International Forum of Researchers and Lecturers, 2024)
: Palm oil theft is a serious problem faced by plantation companies, especially in PTPN II, Pagar Merbau II Village, Pagar Merbau District, Deli Serdang Regency. This study aims to analyze the Law Enforcement of Palm Oil Theft of PTPN II Pagar Merbau II, Pagar Merbau District, Deli Serdang Regency (Case Study of Decision Number 2/Pid.C/2024/PN Lbp). The research method used is a qualitative approach with descriptive analysis. Data were collected through interviews with related parties, studies of court decision documentation, and direct observation of conditions in the field. The analysis was carried out to identify the perpetrators' modus operandi, the effectiveness of the law enforcement system, and the impact of the sanctions given. The results of the study show that palm oil theft is carried out in various modes that are often organized. Law enforcement involves cooperation between companies, security forces, and the community, but still requires improvement in terms of supervision and rapid response to reports of theft. Decision Number 2/Pid.C/2024/PN Lbp provides an overview of the strict application of law against perpetrators, where sanctions not only serve to punish but also to prevent similar crimes in the future. The conclusion of this study is that an effective law enforcement system requires close collaboration between all relevant parties and increased asset protection regulations. With the right steps, it is hoped that palm oil theft can be minimized, supporting the sustainability of the palm oil industry in Indonesia.